2009
DOI: 10.1111/j.1468-3083.2009.03096.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoerythrocyte sensitization syndrome (Gardner-Diamond syndrome): review of the literature**

Abstract: A review of the literature concerning psychogenic purpura is presented. The diagnosis is usually based on typical anamnestic data, clinical presentation (painful inflammatory skin lesions, which progressed to ecchymoses during the next 24 h) and positive diagnostic tests with intracutaneous injections of 80% solution of washed autologous erythrocytes. No pathological findings of blood coagulation parameters are usually detected. Histopathological evaluations of lesional biopsies revealed non-specific changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 56 publications
1
70
0
2
Order By: Relevance
“…[2] Auto-sensitization of patients to their own blood, mainly to phosphatidylserine (phosphoglyceride of red blood cell (RBC) membrane) plays an important role in the pathogenesis. [1] Struneckα et al ., showed that more than 50% of the erythrocyte phosphatidylserine of patients with GDS was redistributed on the outer leaflet of the cell membrane. They also found disorder in cytoskeleton organization of RBCs in such patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Auto-sensitization of patients to their own blood, mainly to phosphatidylserine (phosphoglyceride of red blood cell (RBC) membrane) plays an important role in the pathogenesis. [1] Struneckα et al ., showed that more than 50% of the erythrocyte phosphatidylserine of patients with GDS was redistributed on the outer leaflet of the cell membrane. They also found disorder in cytoskeleton organization of RBCs in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have revealed auto-sensitization to hemoglobin and deoxyribonucleic acid. [13] Merlen suggested that fluctuations in the kallikerin-kinin system lead to disturbance in the tonus regulation of the venous capillaries. [4] Also there is disturbance in the fibrin synthesis in the endothelium, formation of defective structures of capillary walls and extravasation of erythrocytes carrying sensitizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A positive erythrocyte autosensitization test is a distinctive, though not characteristic finding of patients with GDS. 3,4 The pathophysiological mechanism underlying the erythrocyte autosensitization in GDS is not known. Phosphatidylserine a phosphoglyceride of red blood cell membrane is considered to play an important role in the pathogenesis of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner-Diamond-syndrome ("painful ecchymosis syndrome", "psychogenic purpura" or "painful bruising syndrome") was originally attributed to an autoimmune mechanism ("auto-erythrocyte sensitization syndrome"), but has now been classified as a factitious disorder (32,33).…”
Section: Obsessive Compulsive Spectrum Disorders (Ocsd)mentioning
confidence: 99%